(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this article discusses the concept of the digital economy, its economic essence and development issues. In addition, digital technologies not only improve the quality of products and services, but also reduce overhead costs. At the same time, the most serious problem hindering the development of the country - corruption - also plays a big role in the loss of misfortune.